Nitretação por Descargas Elétricas (EDM) do Duralumínio AA 2011 - Morales, Freddy Alejandro Portillo (2019)
The aim of this work was to evaluate the possibility of implanting nitrogen in samples of an aluminum alloy AA 2011 (Al-Cu) through electric discharges generated by the EDM process. Tests were performed with a sink-EDM machine using a solution of deionized water with urea as the dielectric fluid and source of nitrogen. The electrode used was of ultrafine grain graphite with negative polarity. Nitriding by electrical discharge - NDE was carried out under different alloy conditions: solubilized, annealed, aged and work hardened. After NDE, characterization techniques such as micrographic analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), dispersive energy spectrometry (EDS) and Vickers microhardness were used. The results showed that the thermal treatment of aging promotes the incorporation of nitrogen in the material, creating a layer rich in nitrides with a thickness of the order of 68 μm and a microhardness of approximately 117 HV, due to the generation of distortions in the crystalline lattice of the material caused by the formation of coherent precipitates in aging. The results also showed that the hardening of the material promoted the creation of an oxide layer (Al2O3) with a hardness of approximately 1600 HV and a recrystallized zone (ZR) thickness of 479 μm. Thus, it can be concluded that it is possible to implant nitrogen in the duralumin AA 2011 in the condition as aged through electric discharges using an EDM machine.